2016
DOI: 10.5114/jcb.2016.57816
|View full text |Cite
|
Sign up to set email alerts
|

WBRT vs. APBI: an interim report of patient satisfaction and outcomes

Abstract: PurposeTo determine differences in patient's reported quality of life and self-reported breast cosmesis between whole breast radiation therapy (WBRT) and accelerated partial breast irradiation (APBI) via single and multi-lumen high-dose-rate (HDR) brachytherapy for women with early stage breast cancer.Material and methodsPatient information was retrospectively reviewed and survey data were prospectively collected for women treated between 2004 to 2014 (APBI) and 2012 to 2014 (WBRT). Criteria for APBI treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…The estimated cost of external beam APBI is $6578 and $13 506 for multifraction intracavitary brachytherapy compared to $13 358 for SWBI . Although the cost of multifraction intracavitary brachytherapy may not be significantly different from SWBI, there is evidence that APBI may offer improvements in social functioning, personal finances, body image, improved energy, cosmetic satisfaction, overall self‐image as well as lower risk of lymphedema compared to SWBI . Recently, Manyam et al utilized the SEER database to evaluate the proportion of patients who would be eligible for APBI and found that 74.6% of women with early‐stage breast cancer would be eligible based on ABS and GEC‐ESTRO guidelines and 41.2% would be eligible based on the 2016 ASTRO guidelines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated cost of external beam APBI is $6578 and $13 506 for multifraction intracavitary brachytherapy compared to $13 358 for SWBI . Although the cost of multifraction intracavitary brachytherapy may not be significantly different from SWBI, there is evidence that APBI may offer improvements in social functioning, personal finances, body image, improved energy, cosmetic satisfaction, overall self‐image as well as lower risk of lymphedema compared to SWBI . Recently, Manyam et al utilized the SEER database to evaluate the proportion of patients who would be eligible for APBI and found that 74.6% of women with early‐stage breast cancer would be eligible based on ABS and GEC‐ESTRO guidelines and 41.2% would be eligible based on the 2016 ASTRO guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…9 Although the cost of multifraction intracavitary brachytherapy may not be significantly different from SWBI, there is evidence that APBI may offer improvements in social functioning, personal finances, body image, improved energy, cosmetic satisfaction, overall self-image as well as lower risk of lymphedema compared to SWBI. 10 | 809…”
Section: Discussionmentioning
confidence: 99%
“…The results of 5-year follow-up showed that there was no significant difference between the two groups in IBTR and OS, but APBI-IMRT had significantly better performance in acute and chronic toxicities and cosmetic effects. Bitter et al ( 20 ) enrolled 242 patients with breast cancer and found that the chronic lymphedema, self-confidence, and fatigue in the APBI group were significantly less than those in the WBI group in the 1-year follow-up. In the second year, the cosmetic effects of breast appearance in the APBI group were significantly better than those in the WBI group, and there was no significant difference in the recurrence rate between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life is a vital consideration when patients are choosing their breast cancer treatments. Bitter et al[ 53 ] analyzed self-reported cosmetic outcomes for the treated breast and quality of life for patients treated with WBI or APBI via single and multilumen HDR brachytherapy. Two hundred and forty-two patients between 2004 and 2014 with early breast cancer treated with APBI were compared to 59 matched patients treated with WBI from 2012 to 2014.…”
Section: Other Considerationsmentioning
confidence: 99%